The tragedy of american diplomacy - Williams, William Appleman ([S.l.] : W. W. Norton & Company, 1988)
One of the first modern historians to integrate economic realities into the study of American foreign policy, William Appleman Williams has been a diplomatic historian of major influence since the first publication of The Tragedy of American Diplomacy . In this pioneering book, "the man who has really put the counter-tradition together in its modern form" ( Saturday Review ) examines the profound contradictions between America's ideals and its uses of its vast power, from the Open Door Notes of 1898 to the Bay of Pigs and the Vietnam War.